Strategies for a sustainable future in the footwear industry in the face of greenhouse gas emissions (GHG) (Sustainability in Debate, 2024)
In spite of the efforts of the footwear and textile industries to understand their greenhouse gas (GHG) emissions and develop reduction strategies, knowledge on the subject is still incipient. Given this scenario, this paper aims to identify, quantify, and present the main sources of GHG in this economic sector, followed by proposing solutions aimed at more efficient management. A qualitative and quantitative study was conducted with four companies in southern Brazil to achieve this purpose. Among the main sources of emissions are fuel and energy consumption. The main reduction alternatives include searching for alternative fuels and considering energy generation through clean sources. It is clear that implementing initiatives aimed at reducing emissions is not a simple task. However, the research highlighted the technical feasibility of new forms of production with a reduced environmental impact.